The Utilization of Soybean Aircraft Waste as A Additional Material in The Process of Manufacturing Goat Feed Materials - Intan Fatimah Azzahra intan; Zulia Wirdani Putri Nasution; Revina Yani Tarigan; Muhammad Haris; Ulfayani Mayasari (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2022)
The processing process in industry does not only produce the main product but also produces residual production which is usually not used anymore and is called waste. Soybean aircraft waste is a of tempe production by 10% of the total amount of soybean aircraft waste. Environmental problems caused by waste and also the supply of imported feed at a fairly high price underlies researchers to make nutrient-rich feed products by utilizing soybean aircraft waste. The Research content contained in soybean aircraft waste in the form of energy is 306.48 kcal/kg, crude protein 14.45%, fat 3.15% and crude fiber 47.01% . The purpose of this study is to produce a produce a product that is expected to be a solution in reducing waste from the production of soybeans as an additive ]in feed processing. The Methods used in this study is a qualitative descriptive study. The Result in a this journal is additional feed product using soybean aircraft waste that provided benefits for increasing appetite, milk production and meat quality in livestock.